New narrowly distributed species of Myrcia s.l. (Gomidesia clade, Myrtaceae) from the Atlantic Forest of southeastern Brazil - Amorim, Bruno S.; Alves, Marccus (Phytotaxa, 2018)
Two new species of Myrcia s.l. from the Atlantic Forest of southeastern Brazil are here described and illustrated. Myrcia longisepala and M. rogersiana share morphological features which place them in the Gomidesia clade. The species are recorded for lowland and submontane forests in the Atlantic Forest. Myrcia longisepala is morphologically related to M. congestiflora, but differs by its smaller leaves, fewer secondary leaf veins, smaller petioles and fruits. Myrcia rogersiana is morphologically related to M. springiana, but differs by its reduced inflorescence main axis and flowers clustered at the apex of the inflorescence. Distribution maps and conservation assessments based on IUCN criteria are also given.